THE RELATIONSHIP BETWEEN THE LEGAL REGIME OF A LAND PARCEL AND LAND PROTECTION OBLIGATIONS - NARYSHEVA Natalya Germanovna (Правовое государство: теория и практика)
The current issues that provide a scientific basis for improving land management are: determining the relationship between the concepts of land protection and environmental protection, which also includes land as a component of the natural environment; substantiating the differentiation of norms of land and environmental law in a narrow sense with regard to land protection; establishing the limits of differentiation of legal norms governing land protection, depending on their legal regime. Purpose: to substantiate the differentiation of norms of land and environmental law in a narrow sense with regard to land protection; to identify the specifics of the methods of legal impact used in the legal regulation of land protection; to establish the relationship between the legal regime of land and obligations for its protection. Methods: empirical methods of comparison, description, interpretation; theoretical methods of formal and dialectical logic; specific scientific methods: legal-dogmatic and interpretation of legal norms. Results: the article reveals that the protection of lands from negative impact on the environment should constitute a subject of environmental law in a narrow sense, since in this case the negative impact is carried out on lands as a component of a complex environmental object, and the relevant legal requirements are conditioned by the type of activity resulting in negative impact, as well as by the nature of this negative impact. Rational use is ensured by compliance with the legal regime of a land parcel. The main elements of the legal regime of a land parcel are a meaningful reference point for determining measures aimed at restoring the disturbed state of lands.